The Influence of Perceived Social Support on Loneliness Among Students Who Have Confided in Artificial Intelligence - Pinky Yohanna Naibaho; Karina Meriem Beru Brahmana (Badan Penerbit STIEPARI Press, 2025)
Students today are increasingly exposed to both academic and social pressures that arise from rapid environmental and contextual changes within educational settings. These pressures often create psychological burdens that can manifest in negative emotional states, such as feelings of loneliness, especially when students perceive that they lack sufficient social support to help them adapt and cope with such challenges. Loneliness, in turn, can reduce well-being, hinder social functioning, and negatively affect academic performance. In recent years, with the advancement of digital technology, some students have turned to Artificial Intelligence (AI) systems as an alternative outlet for sharing personal feelings, confiding in AI chatbots when they feel isolated or unsupported. While this may provide temporary relief, the presence of social support from peers, family, and significant others is still considered a crucial protective factor against loneliness. This study was conducted to examine the effect of perceived social support on loneliness among students who reported having previously confided in AI. A quantitative approach was employed, using purposive sampling to target students fitting the criteria. Data were gathered through online questionnaires distributed to 384 respondents from various academic backgrounds. To test the research hypothesis, simple linear regression analysis was performed, enabling the exploration of the direct relationship between perceived social support and loneliness in the context of AI-mediated coping behaviors. The results of the analysis indicated that perceived social support has a negative and significant effect on loneliness among students who have confided in AI. Specifically, perceived social support accounted for 34.3% of the variance in loneliness levels. This finding suggests that when students perceive stronger and more reliable social support, their tendency to experience loneliness decreases, even if they also utilize AI as an outlet for self-disclosure.